The mediating role of customer satisfaction in the relationship between product quality, brand image, and brand loyalty: A study of Eiger outdoor gear - Rista Nabilluziyah; Saino Saino (Institute of Computer Science (IOCS), 2026)
This study examines how product quality and brand image influence consumer loyalty toward outdoor products, with consumer satisfaction serving as a mediating variable. The study is motivated by the rapid growth of the outdoor product market driven by healthy lifestyle trends, and it also responds to previous research findings that remain inconsistent within the context of the outdoor equipment industry. The research method employed a quantitative causal design using purposive sampling of 140 students who use Eiger products at Surabaya State University, Airlangga University, and the Institute of Technology 10 November, following prior validation and reliability testing of the instrument on 30 samples. The data was then analyzed using descriptive and inferential statistics in SmartPLS 4. The results indicate that product quality and brand image have a positive and significant influence on loyalty, with consumer satisfaction acting as a partial mediator. These findings clarify the mechanism by which loyalty does not form automatically without user satisfaction. This finding confirms that companies cannot rely solely on quality and brand image but must also generate genuine satisfaction as the key to achieving loyalty. Therefore, Eiger needs to align its brand reputation with actual performance in the field to meet the specific expectations of its critical student consumers